Architectural B-cell organization in skeletal muscle identifies subtypes of dermatomyositis. Issue 3 (May 2018) - Radke, Josefine; Koll, Randi; Preuße, Corinna; Pehl, Debora; Todorova, Kremena; Schönemann, Constanze; Allenbach, Yves; Aronica, Eleonora; de Visser, Marianne; Heppner, Frank L.; Weis, Joachim; Doostkam, Soroush; et al.
Abstract : Objective: To study the B-cell content, organization, and existence of distinct B-cell subpopulations in relation to the expression of type 1 interferon signature related genes in dermatomyositis (DM). Methods: Evaluation of skeletal muscle biopsies from patients with adult DM (aDM) and juvenile DM (jDM) by histology, immunohistochemistry, electron microscopy, and quantitative reverse-transcription PCR. Results: We defined 3 aDM subgroups—classic (containing occasional B cells without clusters), B-cell–rich, and follicle-like aDM—further elucidating IM B-lymphocyte maturation and immunity. The quantity of B cells and formation of ectopic lymphoid structures in a subset of patients with aDM were associated with a specific profile of cytokines and chemokines involved in lymphoid neogenesis. Levels of type 1 interferon signature related gene expression paralleled B-cell content and architectural organization and link B-cell immunity to the interferon type I signature. Conclusion: These data corroborate the important role of B cells in DM, highlighting the direct link between humoral mechanisms as key players in B-cell immunity and the role of type I interferon–related immunity.